Kontrak Asuransi - Anisa Rahmi Ramadhanti; Amalia Rahmasanti Utari; Ajeng Sekar Ardiningrum; Ni Made Swasti Mega Putri; Wafa Hadiya Sabila; Galuh Tresna Murti (CV. Ulil Albab Corp, 2022)
Insurance is a contract under which one party (the insurer) accepts significant insurance risk from another party (the policyholder) by agreeing to a contract to compensate the policyholder if certain definite future events (the insured event) adversely affect the policyholder. This study aims to identify and analyze the application of IFRS and PSAK consisting of PSAK 74, PSAK 28, PSAK 36, IFRS 4, and IFRS 17 relating to insurance contracts in financial statements in Indonesia. This research is a descriptive qualitative writing method with secondary data collection from several journals with the theme of the insurance contract concept by using a literature study. The method used in this research is purposive sampling. Based on the results of this literature study, it can be ascertained that accounting standards have an important role to regulate all insurance contracts.